Tunable size and spectral properties of fluorescent nanoGUMBOS in modified sodium deoxycholate hydrogels - Das, Susmita (Langmuir : the ACS journal of surfaces and colloids, 2012)
Microstructures of sodium deoxycholate hydrogels were altered considerably in the presence of variable tris(hydroxymethyl)aminomethane (TRIS) concentrations. These observations were confirmed by use of X-ray diffraction, polarized optical microscopy, rheology, and differential scanning calorimetry measurements. Our studies reveal enhanced gel crystallinity and rigidity with increasing TRIS concentrations. The tunable hydrogel microstructures obtained under various conditions have been successfully utilized as templates to synthesize cyanine-based fluorescent nanoGUMBOS (nanoparticles from a group of uniform materials based on organic salts). A systematic variation in size (70-200 nm), with relatively low polydispersity and tunable spectral properties of [HMT][AOT] nanoGUMBOS, was achieved by use of these modified hydrogels. The gel microstructures are observed to direct the size as well as molecular self-assembly of the nanomaterials, thereby tuning their spectral properties. These modified hydrogels were also found to possess other interesting properties such as variable morphologies ranging from fibrous to spherulitic, variable degrees of crystallinity, rigidity, optical activity, and release profiles which can be exploited for a multitude of applications. Hence, this study demonstrates a novel method for modification of sodium deoxycholate hydrogels, their applications as templates for nanomaterials synthesis, as well as their potential applications in biotechnology and drug delivery